ETHNOBOTANICAL SURVEY OF MEDICINAL PLANTS USED IN THE MANAGEMENT OF HYPERTENSION IN THE MARITIME REGION OF TOGO - Gbekley, Holaly E.; Karou, Simplice D.; Katawa, Gnatoulma; Tchacondo, Tchadjobo; Batawila, Komlan; Ameyapoh, Yaovi; Simpore, Jacques (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Hypertension is one of the most common chronic diseases in modern societies and there is evidence that its incidence and severity are increasing. This survey was conducted to investigate the plants used by the Togolese traditional healers to treat the disease.Method: From January to June 2016, an ethnobotanical survey was conducted using a semi-structured questionnaire with traditional healers (TH) in the southern region of Togo. The importance of the plants was assessed by the calculation of the use value (UV).Results: In Total, 128 TH male and female were interviewed and 116 plants species belonging to 46 families were identified as treating hypertension. The most represented families were: Fabaceae with 16 species followed by Euphorbiaceae and Rutaceae contributing with 8 and 6 species respectively. Based on the calculated use values the most important species were Byrsocarpus coccineus Schum. Et thonn. (UV = 0.47); Crateva religiosa G.Forst. (UV = 0.47), Boerhavia diffusa Engelm. &A.Gray L. (UV = 0.47), Xylopia aethiopica A. Rich. (UV = 0.42), Mangnifera indica L. (UV = 0.38). The leaves and the roots were the parts of plant predominantly used to prepare the recipes, mainly decoctions administrated by oral route. Clinical manifestations such as dizzy spells, swarming, loss of consciousness, severe headache, severe anxiety and shortness of breath, nosebleed, and fear of heights were used by TH to diagnose the disease.Conclusion: This study showed initial evidence of the use of plant materials by Togolese TH to treat hypertension. These results constitute a database for pharmacological screenings with the aim of developing new therapies.